2018
DOI: 10.1111/pim.12527
|View full text |Cite
|
Sign up to set email alerts
|

Anisakis pegreffii impacts differentiation and function of human dendritic cells

Abstract: Human dendritic cells (DCs) show remarkable phenotypic changes when matured in the presence of helminth-derived products. These modifications frequently elicited a polarization towards Th2 cells and regulatory T cells thus contributing to immunological tolerance against these pathogens. In this study, the interaction between DCs and larvae of the zoonotic anisakid nematode Anisakis pegreffii was investigated. A. pegreffii larvae were collected from fish hosts, and monocyte-derived DCs were cocultured in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 53 publications
3
18
0
Order By: Relevance
“…The same monoclonal CD83 antibody used in the present work identified DC in the paracortical area of lymph nodes displaying a marked cytoplasmic localization, while it was not detected in macrophages located along the medullary sinuses, and it labelled B cells located in the lymphoid follicles that formed a fine reticulum-a staining pattern consistent with that expected for FDC [13]. In our study, the decreased expression of CD83 in DC and FDC of paracortical areas and germinal centres, respectively at 9 and 18 dpi agrees with the decreased expression of the same cell marker in peritoneal leucocytes from F. hepatica-infected sheep at 3 and 9 dpi [54] and with the decrease in the expression of CD83 in monocyte-derived DC cocultured in the presence Anisakis pegreffi live larvae and their crude extracts [61], as well as T. multiceps [62] and T. spiralis [63]. Since the expression of the CD83 molecule in mature DC could have a specialized function during antigenic presentation, contributing to lymphoid activation [64], reduced CD83 expression during F. hepatica infection in sheep suggests a modulatory effect that impairs antigenic presentation and, therefore, the host immune response during the early stages of infection.…”
Section: Discussionsupporting
confidence: 89%
“…The same monoclonal CD83 antibody used in the present work identified DC in the paracortical area of lymph nodes displaying a marked cytoplasmic localization, while it was not detected in macrophages located along the medullary sinuses, and it labelled B cells located in the lymphoid follicles that formed a fine reticulum-a staining pattern consistent with that expected for FDC [13]. In our study, the decreased expression of CD83 in DC and FDC of paracortical areas and germinal centres, respectively at 9 and 18 dpi agrees with the decreased expression of the same cell marker in peritoneal leucocytes from F. hepatica-infected sheep at 3 and 9 dpi [54] and with the decrease in the expression of CD83 in monocyte-derived DC cocultured in the presence Anisakis pegreffi live larvae and their crude extracts [61], as well as T. multiceps [62] and T. spiralis [63]. Since the expression of the CD83 molecule in mature DC could have a specialized function during antigenic presentation, contributing to lymphoid activation [64], reduced CD83 expression during F. hepatica infection in sheep suggests a modulatory effect that impairs antigenic presentation and, therefore, the host immune response during the early stages of infection.…”
Section: Discussionsupporting
confidence: 89%
“…This might suggest that live larvae trigger different immune recognition and activation pathways than crude extracts or even secretory/excretory products ( 53 ). This hypothesis is supported by a recent study where dendritic cell (DC) cytokine and chemokine secretion was conditioned by live A. pegreffii larvae or crude extract ( 54 ). Interestingly, the autologous CD4 + T cells that were stimulated by DCs differentiated in the presence of live larvae or crude extract but failed to produce IL4, IL17, and IL10.…”
Section: Discussionmentioning
confidence: 59%
“…In particular, macrophage C-type lectin (MGL) has been identified as a selective binder of the carbohydrate residue GalNAc-O-S/T (Tn) carried by several parasites as well as expressed by cancer cells [51,52,66]. Further, it has been found that the interaction between the MGL lectin expressed by dendritic cells (DCs) and the parasite A. pegreffii likely induces a Th-2 switch, involved in IgE-mediated responses against this parasite [50]. Thus, since the transcript levels of A.peg-7 in A. pegreffii seem to be maintained in the selected temperature-conditions investigated in the present study, its gene expression would rather be modulated by the host (both of intermediate and definitive/accidental human hosts) immune response.…”
Section: Discussionmentioning
confidence: 99%
“…would be able to induce and regulate the Th-2 polarising response associated with Anisakis infection in the accidental host (humans) [64]. On the other hand, the capacity of A. pegreffii larvae to impair human DC cell biology and function has also been shown experimentally [50], suggesting possible up-regulation of this gene under the effective cellular immune response of the homeothermic human host.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation